Do We Really Understand What the Gross Enrollment Ratio Measures? - Schendel, Rebecca; Alcott, Benjamin (International Higher Education, 2024)
<h3 id="the-gross-enrollment-ratio-ger-is-often-misunderstood-as-a-valid-measure-of-undergraduate-enrollment-in-fact-the-measurement-of-ger-includes-students-well-beyond-typical-undergraduate-age-encompasses-enrollment-in-associate-bachelor-master-and-doctoral-degrees-and-lacks-consistency-in-whether-international-students-are-counted-in-their-home-or-host-country-this-raises-important-concerns-about-the-policy-implications-of-ger-measures-and-questions-about-how-to-develop-more-conceptually-meaningful-indicators-in-future" data-pm-slice="1 1 []">The gross enrollment ratio (GER) is often misunderstood as a valid measure of undergraduate enrollment. In fact, the measurement of GER includes students well beyond typical undergraduate age; encompasses enrollment in associate, bachelor, master, and doctoral degrees and lacks consistency in whether international students are counted in their home or host country. This raises important concerns about the policy implications of GER measures and questions about how to develop more conceptually meaningful indicators in future.